Teachers’ Management In Planning and Implementing for the Success of EFL Learning - Kardena, Absharini (Beyond Words, 2019)
Group work as one of teaching techniques on the framework of communicative approach is believed to be an effective model for building students’ communicative competence. The process of applying this technique needs high skills of management of an English teacher. The English teacher has autonomy to plan and implement the group work in order to achieve an objective of EFL learning. Since the autonomy handled by the teacher, any decisions and actions taken should be considered for assuring the success of EFL learning. The teachers’ management in planning and implementing group work influenced the successful of this teaching technique. This article, which is derived and further developed based on research conducted in 2013, analyzes and discusses the way the teachers plan and implement group work for the success of EFL learning at MAN Kota Solok. The research was conducted in terms of qualitative research by involving 5 English teachers at MAN kota Solok. The research found that the teachers still needs some guidance and improvements in planning and implementing group work for students at MAN Kota Solok